An alternative model for open science: Theaters, trees, rhizomes, and rhetorical machines - Fernández Galán Montemayor, Carmen; García Guerrero, Montserrat (Nawi, 2023)
This text analyses the representations about open science as a new paradigm of knowledge, and a journey through the tradition of organization of knowledge in the West is made. Based on these models, it is intended to build one of its own, within the framework of the epistemic change from paradigms to turns (linguistic, semiotic, pictorial and affective).The methodological strategy consists of a contrastive analysis of the history of images of knowledge with the current debate on open science. As preliminary results, two proposals for approaching different discursive genres are presented: a dystopian narrative and a binary poem as alternative multimodal models for science.